Ovarian preservation techniques for female pelvic radiotherapy techniques: a critical review. Issue 1 (18th October 2016) - Durrant, A; Bridge, P
Abstract: Introduction: Advances in treatment over recent years have increased the long-term survival of young, female cancer patients; unfortunately these treatments bring a significant risk of ovarian failure and infertility. This literature review aimed to determine the optimal technique for ovarian preservation in pre-menopausal women receiving pelvic radiotherapy (IMRT). The traditional method comprises surgical transposition; IMRT and other emerging techniques may offer alternative non-invasive means of sparing ovaries and minimising dose. Methods: A critical review of the evidence pertaining to pelvic radiotherapy and ovarian sparing was performed. Evidence was subjected to critical appraisal using the Critical Appraisal Skills Programme tool and thematic analysis of the findings identified key issues. Results: Surgical transposition appears to be a successful method of preserving ovarian function depending on the position of the ovaries outside of the radiation field, the age of the patient and the total dose received by the ovaries. There is limited modern evidence concerning its usage in relation to emerging techniques and technology. The use of IMRT is certainly widespread in the treatment of female pelvic cancers, however, there is no evidence supporting its use for reduction of ovarian dose. Several other studies have attempted to demonstrate new techniques to preserve ovarian function, but no functional outcome measures have reinforced their results. Conclusions: Ovarian transposition has a proven track record for preservation of ovarian function, but the potential value of IMRT as a viable alternative to date remains unexplored. New work should be encouraged to determine the potential value of IMRT as a non-surgical alternative.